Pengaruh Rasio Profitabilitas dan Economic Value Added (EVA) terhadap Harga Saham Syariah pada Perusahaan yang terdaftar di Indonesia Sharia Stock Index Tahun 2013-2014 - Ilmi, Diah Qoriani, Imron Rosyadi, S.E., M.Si (2016)
Research titled "Influence Profitability Ratio and Economic Value Added (EVA) against Sharia Stock Price on companies registered in Indonesia Sharia Stock Index (ISSI) years 2013-2014". Aims to review the independent variabels EVA and Profitability Ratio whether partial and simultaneously againts Sharia stock price on companies registered in ISSI. Included in this study is listed companies in ISSI about 50 companies with showing financial report completely and clearly from the period 2013 and 2014. The method of analysis of data used in this research using analysis the classic assumptions and the multiple linear regression. Test results in calculation t explain that EVA and ROA influential positively and significantly to Sharia Stock Price. Variabel ROE have negative effects and significantly to Sharia Stock Pice. While variable NPM influential positive and not significantly to Sharia Stock Price. Simultaneously variabels EVA, ROA, NPM and ROE influential positively and significantly to Sharia Stock Price.